Spontaneous rupture of lens capsule with dislocation of nucleus in hypermature cataract - Malik, VK; Jhalani, Rishi; Malik, KPS; Gupta, Abhishek (Nepalese Journal of Ophthalmology, 2014)
We report a case of spontaneous rupture of the lens capsule in a woman with hypermature cataract, who presented to us with nucleus dislocation in the posterior chamber of her left eye. The capsule had ruptured inferiorly and the nucleus had slided out of it. The anterior chamber was quiet; and no sign of uveitis was noted. She underwent nucleus extraction and IOL implantation in the sulcus. Spontaneous rupture of the anterior lens capsule that leads to dislocation of the nucleus is a rare complication of hypermature cataracts. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10778 Nepal J Ophthalmol 2014; 6 (2): 95-97